Trigo-Tricks (TT): enhancing mathematics learning via online games - Hisham, Balqis; Hassan, Suraya; Md Saad, Norlaili; Hairom, Juhaidah; Mohamad Hanafi, Nurfatihah (Centre of Foundation Studies, Universiti Teknologi MARA, Cawangan Selangor, Kampus Dengkil 2024, 2024)
ABSTRACT Gamification in mathematics is an interactive pedagogy that can be used to increase students’ interests. In learning mathematical concepts like trigonometric topics, more interactive activities and engagement platforms are proposed to help the students’ understanding. An online game called Trigo-Tricks (TT) was created so that students could play it and concurrently work through the games’ questions. The aim of this study is to examine the students’ interest in learning trigonometric topics which are found to be difficult for them to understand using Trigo-Tricks (TT). This Trigo-Tricks (TT) is designed using the Buildbox platform and it is integrated with trigonometric concepts. A sample of 45 sciences students in the Centre for Foundation Studies, International Islamic University Malaysia (CFS IIUM) will be selected for this study using purposive sampling technique. Overall, the findings support that gamification in mathematics gives a better learning environment and is suitable to be used as educational tools. Students are more likely to explore new learning methods for understanding subject matter compared to traditional methods. For commercialization, this game can be introduced and utilized by all institutions that offer pre-university programme. The game is practical, and it is easy to be accessed by students. As a conclusion, Trigo-Tricks (TT) provides an advantage for students such as increasing the students’ interest and understanding in learning Mathematics.